Cover Feature: Precursor‐Directed Diversification of Cyclic Tetrapeptidic Pseudoxylallemycins (ChemBioChem 21/2018). (25th October 2018) - Guo, Huijuan; Schmidt, Alexander; Stephan, Philipp; Raguž, Luka; Braga, Daniel; Kaiser, Marcel; Dahse, Hans‐Martin; Weigel, Christiane; Lackner, Gerald; Beemelmanns, Christine
Abstract : The cover feature picture shows a fungus‐growing termite nest in the South African savanna, the co‐evolved antagonistic fungus of termites, Pseudoxylaria X802 that grows on natural fungus comb material, and isolated pseudoxylallemycins that contain a rare O ‐homoallenyl‐l ‐tyrosine moiety. A precursor‐directed diversification strategy with para ‐substituted unnatural amino acids resulted in the isolation of 21 new pseudoxylallemycin derivatives showing micromolar antibiotic activity. These results suggest that an unusual promiscuous non‐ribosomal peptide synthase is responsible for their biosynthesis. Bifunctional pseudoxylallemycin derivatives were chemically modified for future target identification. More information the unusual natural products can be found in the full paper by C. Beemelmanns et al. onpage 2307 in Issue 21, 2018 (DOI:10.1002/cbic.201800503 ).